Banks as corporate monitors: Evidence from CEO turnovers in China - Qing He; Jiyuan Huang; Dongxu Li; Liping Lu (Bank of Finland, Institute for Economies in Transition (BOFIT), 2016)
​This paper examines the governance role of banks in replacement of underperforming CEOs in firms listed on Chinese stock exchanges. Under most circumstances, the findings suggest that the presence of outstanding loans does not increase the probability that a poorly performing CEO will be forced out and replaced. However, there is a positive and significant effect if the under-performing firm relies heavily on secured and short-term bank lending. Bank loans increase the likelihood of a forced CEO turnover in private firms, especially where joint-equity banks serve as the main lenders to the firm. There is no similar increase in the probability of a CEO turnover for state-owned firms or firms that borrow mainly from state-owned banks. Thus, where state ownership of banks and listed firms implies inefficiency or reluctance on monitoring borrower performance, there is an opportunity to improve loan contract arrangements to improve the mon-itoring role of lending banks.
URN:NBN:fi:bof-201612271552
Keywords: G21; G30; G32; G38; K22; 330